Preparation method and application for regulating and controlling micro-pore structure of hard carbon negative electrode material

By performing preliminary reaction and carbonization of hard carbon precursor materials in a closed reactor, a closed nanopore structure is formed, which solves the problem of insufficient sodium storage performance of hard carbon in sodium ion batteries, and improves the total capacity and electrochemistry of the material Performance, simplifying process flow and reducing costs.

CN119284866AActive Publication Date: 2025-01-10NINGBO YINGCHUANG SCI & TECH ACHIEVEMENTS TRANSFORMATION SERVICE PARTNERSHIP (LLP)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411187364.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-10
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

Hard carbon has poor sodium storage performance in sodium ion batteries, mainly due to its complex microstructure and inability to form stable sodium compounds, resulting in low specific capacity, which limits its commercial application.

Method used

By performing preliminary reactions and two carbonization treatments on the hard carbon precursor material in a closed reactor, the filling degree and temperature are controlled to form a rich closed nanopore structure and the sodium storage performance of the hard carbon material is improved.

Benefits of technology

The high platform capacity of hard carbon anode material and the first Coulomb efficiency are improved, which reduces the preparation cost, simplifies the process flow, and improves the electrochemical performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284866A_ABST
    Figure CN119284866A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application for regulating and controlling a micro-pore structure of a hard carbon negative electrode material. The preparation method comprises the following steps that a hard carbon precursor material is placed in a closed reactor to be subjected to a primary reaction, a pre-product is obtained, the filling degree of the hard carbon precursor material in the closed reactor is larger than or equal to 40%, when the filling degree is 40%, the temperature of the primary reaction is 350-450 DEG C, and when the filling degree is increased by 5%, the temperature of the primary reaction is 30-50 DEG C; the temperature of the primary reaction is relatively reduced by 20-25 DEG C; and under a protective atmosphere, sequentially carrying out first carbonization treatment and second carbonization treatment on the pre-product to obtain the hard carbon negative electrode material. The invention provides a simpler preparation method, and the prepared hard carbon negative electrode material has a rich closed nano-pore structure, so that the sodium storage performance of the negative electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery energy storage, and in particular to a preparation method and application of a hard carbon negative electrode material for regulating the microscopic pore structure. Background Art

[0002] Sodium-ion batteries have shown broad application prospects in the field of energy storage due to their advantages such as low cost, low temperature and good rate performance. Hard carbon has an interlaced layered structure and pores formed by disordered accumulation of some carbon layers, which can store sodium ions at a lower potential, making it the first choice for negative electrode materials of sodium-ion batteries. However, the microstructure of hard carbon is very complex, consisting of a large number of graphite microcrystals and amorphous nanodomains. + It cannot form stable compounds with these graphite microcrystals, resulting in poor sodium storage performance and low specific capacity, which greatly limits its commercial application.

[0003] In order to improve the sodium storage performance of hard carbon, more sodium adsorption sites can be provided in the high-pressure region (>0.1V) through structural defects, thereby increasing the capacity of the slope section and then the total capacity of the hard carbon, but this will reduce the first coulombic efficiency of the hard carbon. In the low-pressure region (<0.1V), in addition to being intercalated in the graphite microcrystalline layer, sodium ions will also form a large number of quasi-metallic clusters in the form of filling closed nanopores, which will greatly improve the sodium storage performance of hard carbon in the platform stage. Therefore, by precisely controlling the pore structure and forming more closed nanopore structures, it is beneficial to prepare a hard carbon negative electrode with a large platform capacity. However, traditional processes such as the template method and chemical activation method require acid and alkali washing to remove the template and impurity components in the later stage, which will not only cause the collapse of the hard carbon structure, but also increase the preparation cost due to the complexity of the subsequent processing process. Summary of the invention

[0004] Based on this, it is necessary to provide a preparation method and application for regulating the microscopic pore structure of hard carbon negative electrode materials to address the above problems; the present invention proposes a simpler preparation method, so that the prepared hard carbon negative electrode material has a rich closed pore structure, thereby improving the sodium storage performance of the negative electrode material.

[0005] A preparation method for regulating the microscopic pore structure of a hard carbon negative electrode material comprises the following steps:

[0006] Placing a hard carbon precursor material in a closed reactor for a preliminary reaction to obtain a pre-product, wherein the filling degree of the hard carbon precursor material in the closed reactor is greater than or equal to 40%, when the filling degree is 40%, the temperature of the preliminary reaction is 350° C.-450° C., and the temperature of the preliminary reaction is relatively reduced by 20° C.-25° C. for every 5% increase in the filling degree;

[0007] Under a protective atmosphere, the pre-product is subjected to a first carbonization treatment and a second carbonization treatment in sequence to obtain a hard carbon negative electrode material.

[0008] In one embodiment, the filling degree of the hard carbon precursor material in the closed reactor is 50%-90%.

[0009] In one embodiment, the change in the filling degree of the reactants before and after the reaction in the closed reactor is 5%-10%.

[0010] In one embodiment, the hard carbon precursor material includes at least one of a sugar material, a bio-based material, and a resin-based material.

[0011] In one embodiment, the temperature of the preliminary reaction is 150°C-500°C, the heating rate is 1°C / min-10°C / min, and the insulation time is 60min-600min.

[0012] In one embodiment, the temperature of the first carbonization treatment is 500°C-700°C, the heating rate is 1°C / min-10°C / min, and the holding time is less than or equal to 180 minutes.

[0013] In one embodiment, the temperature of the second carbonization treatment is 1000°C-1500°C, the heating rate is 1°C / min-5°C / min, and the holding time is less than or equal to 180 minutes.

[0014] A hard carbon negative electrode material prepared by the preparation method for regulating the microscopic pore structure of the hard carbon negative electrode material as described above, wherein the volume of the closed nanopores in the hard carbon negative electrode material is 0.1 cm 3 / g-0.5cm 3 / g.

[0015] In one embodiment, the volume of the closed nanopores in the hard carbon negative electrode material is 0.15 cm 3 / g-0.4cm 3 / g.

[0016] A hard carbon negative electrode material as described above is used in a sodium ion battery.

[0017] The preparation method described in the present invention performs a preliminary reaction on a hard carbon precursor material having a filling degree greater than or equal to 40% in a closed reactor without liquid, so that the hard carbon precursor material is restricted in expansion and decomposes to release gases such as carbon dioxide, methane, carbon monoxide, hydrogen, ammonia and water vapor, and coordinately regulates the filling degree of the hard carbon precursor material in the closed reactor and the temperature of the preliminary reaction to form a specific high-pressure environment in a limited reaction space, forcing the expansion of the precursor to be restricted, causing contraction of the precursor locally and between molecular layers, which is conducive to promoting the formation of a rich closed pore structure in the structure, thereby accurately regulating the microstructure of the hard carbon material, and the concentrated high-pressure gas molecules can generate cavities between the restricted molecular layers through thermal motion, which is conducive to causing the material pores to tend to produce more micropores and closed nanopore structures during later carbonization, thereby improving the sodium storage performance of the hard carbon material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 This is a scanning electron microscope image of the hard carbon negative electrode material prepared in Example 3 of the present invention;

[0020] Figure 2 This is a scanning electron microscope image of the hard carbon negative electrode material prepared in Example 5 of the present invention;

[0021] Figure 3 This is a scanning electron microscope image of the hard carbon negative electrode material prepared in Example 7 of the present invention;

[0022] Figure 4 This is a scanning electron microscope image of the hard carbon negative electrode material prepared in Comparative Example 1 of the present invention;

[0023] Figure 5 This is a scanning electron microscope image of the hard carbon negative electrode material prepared in Comparative Example 2 of the present invention;

[0024] Figure 6 This is a scanning electron microscope image of the hard carbon negative electrode material prepared in Comparative Example 3 of the present invention;

[0025] Figure 7 This is a charge and discharge curve diagram of the first cycle of a sodium ion battery prepared using the hard carbon negative electrode material of Example 3 of the present invention;

[0026] Figure 8 This is a charge and discharge curve diagram of the first cycle of a sodium ion battery prepared using the hard carbon negative electrode material of Example 5 of the present invention;

[0027] Fig. 9 This is a charge and discharge curve diagram of the first cycle of a sodium ion battery prepared using the hard carbon negative electrode material of Example 7 of the present invention;

[0028] Fig.10 The first cycle charge and discharge curve of a sodium ion battery prepared using the hard carbon negative electrode material of Comparative Example 1 of the present invention;

[0029] Fig.11 The first cycle charge and discharge curve of a sodium ion battery prepared using the hard carbon negative electrode material of Comparative Example 2 of the present invention;

[0030] Fig.12 This is a charge and discharge curve diagram of the first cycle of a sodium ion battery prepared using the hard carbon negative electrode material of Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0031] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0033] The present invention provides a preparation method for regulating the microscopic pore structure of a hard carbon negative electrode material, comprising the following steps:

[0034] S1, placing a hard carbon precursor material in a closed reactor for preliminary reaction to obtain a pre-product, wherein the filling degree of the hard carbon precursor material in the closed reactor is greater than or equal to 40%, when the filling degree is 40%, the temperature of the preliminary reaction is 350° C.-450° C., and the temperature of the preliminary reaction is relatively reduced by 20° C.-25° C. for every 5% increase in the filling degree;

[0035] S2, under a protective atmosphere, subjecting the pre-product to a first carbonization treatment and a second carbonization treatment in sequence to obtain the hard carbon negative electrode material.

[0036] During carbonization, the hard carbon precursor material undergoes structural reorganization and gas generation accompanied by pyrolysis, which will cause changes in the distance between molecules / atoms, increase the internal stress of the material, and thus cause volume expansion, forming an open pore structure, which is not conducive to the storage of sodium ions. Traditional hydrothermal / solvothermal reactions can increase the degree of crosslinking between raw material molecules through the auxiliary reaction of liquid solvents such as ethanol and water, and alleviate the volume expansion of the material to a certain extent. However, the gas generated by the vaporization of these liquids overflows from the precursor material, resulting in the formation of an open pore structure, which is also not conducive to the storage of sodium ions.

[0037] The present invention conducts a preliminary reaction on a hard carbon precursor material with a filling degree greater than or equal to 40% in a closed reactor. When heated, the precursor material expands due to heat, decomposes and releases gas (carbon dioxide, methane, carbon monoxide, hydrogen, ammonia and water vapor, etc.), but due to limited space, the expansion of the precursor is limited, and the material undergoes local contraction on the macroscopic and microscopic layers, and under high temperature and high pressure environment, the precursor molecular layers will further contract, thereby regulating the microstructure of the material. At the same time, the concentrated high-pressure gas molecules can generate cavities between the restricted molecular layers through thermal motion, so that the pores of the material tend to produce more micropores and closed nanopore structures during the later carbonization, which is beneficial to improving the sodium storage performance of the hard carbon material.

[0038] In step S1, preferably, the filling degree of the hard carbon precursor material in the closed reactor is 50%-90%, including any value among 50%, 60%, 70%, 80%, 90% or any range between two values.

[0039] Preferably, the change in the filling degree of the reactants before and after the reaction in the closed reactor is 5%-10%, including any point value among 5%, 6%, 7%, 8%, 9%, 10% or any range value between two of them.

[0040] In one embodiment, the hard carbon precursor material includes but is not limited to at least one of a carbohydrate material, a bio-based material, and a resin-based material. Specifically, the carbohydrate material is preferably starch, the bio-based material is preferably biomass coconut shell powder, and the resin-based material is preferably a synthetic formaldehyde-resorcinol phenolic resin powder.

[0041] In one embodiment, the temperature of the preliminary reaction is 150°C-500°C, the heating rate is 1°C / min-10°C / min, and the insulation time is 60min-600min.

[0042] In one embodiment, after the preliminary reaction, a particle size screening step is further included to make the particle size of the pre-product be 2 μm-80 μm.

[0043] In step S2, the pre-product with a specific preset pore structure is subjected to two-step carbonization treatment in sequence. Preferably, the temperature of the second carbonization treatment is higher than the temperature of the first carbonization treatment, which is more conducive to promoting the preset pore structure to form more closed nanopore structures during the gradual carbonization process, thereby improving the sodium storage performance of the hard carbon material.

[0044] In one embodiment, the temperature of the first carbonization treatment is 500° C.-700° C., the heating rate is 1° C. / min-10° C. / min, and the holding time is less than or equal to 180 min.

[0045] In one embodiment, after the first carbonization treatment, a particle size screening step is further included to make the particle size of the product be 2 μm-50 μm.

[0046] In one embodiment, the temperature of the second carbonization treatment is 1000° C.-1500° C., the heating rate is 1° C. / min-5° C. / min, and the holding time is less than or equal to 180 min.

[0047] In one embodiment, the protective atmosphere includes but is not limited to at least one of nitrogen and argon.

[0048] The present invention provides a hard carbon negative electrode material prepared by the preparation method for regulating the microscopic pore structure of the hard carbon negative electrode material as described above, wherein the volume of the closed nanopores in the hard carbon negative electrode material is 0.1 cm 3 / g-0.5cm 3 / g, preferably 0.15cm 3 / g-0.4cm 3 / g.

[0049] The present invention also provides a hard carbon negative electrode material as described above for use in a sodium ion battery. It is understandable that the sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, wherein the negative electrode sheet uses the hard carbon negative electrode material as an active material.

[0050] It should be noted that the present invention does not limit the preparation method of the negative electrode sheet, and a conventional process can be used. For example, the above-mentioned hard carbon negative electrode material, conductive agent, and binder are mixed in a mass ratio of 80:10:10-94:3:3 to form a slurry, which is applied on the current collector and dried. Among them, the conductive agent includes conductive carbon black, acetylene black, graphite powder, Ketjen black, etc., preferably conductive carbon black. The binder includes but is not limited to at least one of sodium carboxymethyl cellulose, sodium alginate, and polyvinylidene fluoride, preferably sodium carboxymethyl cellulose. The solvent used to prepare the slurry is preferably water. The current collector includes copper foil or aluminum foil, the drying temperature is 60°C-120°C, and the drying time is 1h-20h.

[0051] Specifically, the electrolyte includes a sodium salt and a non-aqueous solvent, and the sodium salt includes but is not limited to NaPF 6 and NaClO 4 At least one of the following, preferably NaPF 6 The non-aqueous solvent includes but is not limited to at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate and diethyl carbonate, preferably a mixture of diethyl carbonate and ethylene carbonate.

[0052] Hereinafter, the preparation method and application of the microstructure of the hard carbon negative electrode material will be further described through the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If the specific conditions are not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0053] Example 1

[0054] Starch is used as a hard carbon precursor material and placed in a high-pressure reactor. The filling degree of starch in the high-pressure reactor is controlled to be 40%. The reactor is sealed and heated to 450°C at a heating rate of 5°C / min and kept warm for 300 minutes. Then, it is cooled to room temperature. The obtained material is sieved through a 100-mesh sieve to obtain a pretreated product.

[0055] The pretreated product was heated to 500°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept warm for 120 minutes, then cooled to room temperature, and ground through a 400-mesh sieve. Then, the pretreated product was heated to 1400°C at a heating rate of 2°C / min under a nitrogen atmosphere, kept warm for 120 minutes, and then cooled to room temperature to obtain a regulated hard carbon negative electrode material.

[0056] Example 2

[0057] Starch is used as a hard carbon precursor material and placed in a high-pressure reactor. The filling degree of starch in the high-pressure reactor is controlled to be 70%. The reactor is sealed and heated to 300°C at a heating rate of 5°C / min and kept warm for 300 minutes. Then, it is cooled to room temperature. The obtained material is sieved through a 100-mesh sieve to obtain a pretreated product.

[0058] The pretreated product was heated to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, kept warm for 120 minutes, then cooled to room temperature, and ground through a 400-mesh sieve. Then, the pretreated product was heated to 1400°C at a heating rate of 2°C / min under a nitrogen atmosphere, kept warm for 120 minutes, and then cooled to room temperature to obtain a regulated hard carbon negative electrode material.

[0059] Example 3

[0060] Starch is used as a hard carbon precursor material and placed in a high-pressure reactor. The filling degree of starch in the high-pressure reactor is controlled to be 100%. The reactor is sealed and heated to 200°C at a heating rate of 5°C / min and kept warm for 300 minutes. Then, it is cooled to room temperature. The obtained material is sieved through a 100-mesh sieve to obtain a pretreated product.

[0061] The pretreated product was heated to 500°C at a heating rate of 10°C / min under a nitrogen atmosphere, kept warm for 120 minutes, then cooled to room temperature, and ground through a 400-mesh sieve. Then, the pretreated product was heated to 1400°C at a heating rate of 2°C / min under a nitrogen atmosphere, kept warm for 120 minutes, and then cooled to room temperature to obtain a regulated hard carbon negative electrode material.

[0062] Example 4

[0063] Biomass coconut shell powder is used as a hard carbon precursor material, placed in a high-pressure reactor, and the filling degree of the biomass coconut shell powder in the high-pressure reactor is controlled to be 60%. The reactor is sealed, and the temperature is increased to 400°C at a heating rate of 5°C / min and kept for 300 minutes, then cooled to room temperature, and the obtained material is passed through a 100-mesh sieve to obtain a pretreated product.

[0064] The pretreated product was heated to 600°C at a heating rate of 10°C / min under a nitrogen atmosphere, kept warm for 120 minutes, then cooled to room temperature, and ground through a 400-mesh sieve. Then, the pretreated product was heated to 1400°C at a heating rate of 2°C / min under a nitrogen atmosphere, kept warm for 120 minutes, and then cooled to room temperature to obtain a regulated hard carbon negative electrode material.

[0065] Example 5

[0066] Biomass coconut shell powder is used as a hard carbon precursor material, placed in a high-pressure reactor, and the filling degree of the biomass coconut shell powder in the high-pressure reactor is controlled to be 80%. The reactor is sealed, and the temperature is increased to 300°C at a heating rate of 5°C / min and kept for 300 minutes, then cooled to room temperature, and the obtained material is passed through a 100-mesh sieve to obtain a pretreated product.

[0067] The pretreated product was heated to 600°C at a heating rate of 10°C / min under a nitrogen atmosphere, kept warm for 120 minutes, then cooled to room temperature, and ground through a 400-mesh sieve. Then, the pretreated product was heated to 1400°C at a heating rate of 2°C / min under a nitrogen atmosphere, kept warm for 120 minutes, and then cooled to room temperature to obtain a regulated hard carbon negative electrode material.

[0068] Example 6

[0069] Phenolic resin powder is used as a hard carbon precursor material, placed in a high-pressure reactor, and the filling degree of the phenolic resin powder in the high-pressure reactor is controlled to be 60%. The reactor is sealed, and the temperature is increased to 380°C at a heating rate of 5°C / min and kept for 300 minutes, then cooled to room temperature. The obtained material is sieved through a 100-mesh sieve to obtain a pretreated product.

[0070] The pretreated product was heated to 700°C at a heating rate of 10°C / min under a nitrogen atmosphere, kept warm for 120 minutes, then cooled to room temperature, and ground through a 400-mesh sieve. Then, the pretreated product was heated to 1400°C at a heating rate of 2°C / min under a nitrogen atmosphere, kept warm for 120 minutes, and then cooled to room temperature to obtain a regulated hard carbon negative electrode material.

[0071] Example 7

[0072] Phenolic resin powder is used as a hard carbon precursor material and placed in a high-pressure reactor. The filling degree of the phenolic resin powder in the high-pressure reactor is controlled to be 90%. The reactor is sealed and heated to 250°C at a heating rate of 5°C / min and kept warm for 300 minutes. Then, it is cooled to room temperature. The obtained material is sieved through a 100-mesh sieve to obtain a pretreated product.

[0073] The pretreated product was heated to 700°C at a heating rate of 10°C / min under a nitrogen atmosphere, kept warm for 120 minutes, then cooled to room temperature, and ground through a 400-mesh sieve. Then, the pretreated product was heated to 1400°C at a heating rate of 2°C / min under a nitrogen atmosphere, kept warm for 120 minutes, and then cooled to room temperature to obtain a regulated hard carbon negative electrode material.

[0074] Comparative Example 1

[0075] The difference between Comparative Example 1 and Example 3 is that the starch is placed in a crucible, heated to 200° C. at a heating rate of 5° C. / min and kept warm for 300 min, then cooled to room temperature, and the obtained material is sieved through a 100-mesh sieve to obtain a pretreated product.

[0076] The pretreated product was heated to 500°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept warm for 120 minutes, cooled to room temperature, and ground through a 400-mesh sieve. Then, the pretreated product was heated to 1400°C at a heating rate of 2°C / min under a nitrogen atmosphere, kept warm for 120 minutes, and cooled to room temperature to obtain a hard carbon negative electrode material.

[0077] Comparative Example 2

[0078] The difference between Comparative Example 2 and Example 5 is that the biomass coconut shell powder is placed in a crucible, heated to 300°C at a heating rate of 5°C / min and kept warm for 300 minutes, then cooled to room temperature, and the obtained material is sieved through a 100-mesh sieve to obtain a pretreated product.

[0079] The pretreated product was heated to 600°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept warm for 120 minutes, cooled to room temperature, and ground through a 400-mesh sieve. Then, the pretreated product was heated to 1400°C at a heating rate of 2°C / min under a nitrogen atmosphere, kept warm for 120 minutes, and cooled to room temperature to obtain a hard carbon negative electrode material.

[0080] Comparative Example 3

[0081] The difference between Comparative Example 3 and Example 7 is that the phenolic resin powder is placed in a crucible, heated to 250° C. at a heating rate of 5° C. / min and kept warm for 300 min, then cooled to room temperature, and the obtained material is sieved through a 100-mesh sieve to obtain a pretreated product.

[0082] The pretreated product was heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept warm for 120 minutes, cooled to room temperature, and ground through a 400-mesh sieve. Then, the pretreated product was heated to 1400°C at a heating rate of 2°C / min under a nitrogen atmosphere, kept warm for 120 minutes, and cooled to room temperature to obtain a hard carbon negative electrode material.

[0083] Comparative Example 4

[0084] The difference between Comparative Example 4 and Example 3 is that the filling degree of starch in the autoclave is 20%. The temperature is raised to 500°C at a heating rate of 5°C / min and kept for 300 minutes, then cooled to room temperature, and the obtained material is passed through a 100-mesh sieve to obtain a pretreated product.

[0085] The pretreated product was heated to 500°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept warm for 120 minutes, cooled to room temperature, and ground through a 400-mesh sieve. Then, the pretreated product was heated to 1400°C at a heating rate of 2°C / min under a nitrogen atmosphere, kept warm for 120 minutes, and cooled to room temperature to obtain a hard carbon negative electrode material.

[0086] The porous hard carbon negative electrode materials prepared in Examples 3, 5, 7 and Comparative Examples 1, 2, 3 were characterized by morphology. Figure 1-6 The porous hard carbon negative electrode materials prepared in Examples 1-7 and Comparative Examples 1-4 were subjected to true density tests and performance tests. The test results are shown in Tables 1 and Figure 7-12 shown.

[0087] (1) The volume of closed nanopores can be calculated by testing the true density of hard carbon using the formula:

[0088]

[0089] Among them, 2.26cm 3 / g is the true density of ideal graphite.

[0090] (2) Performance test: Weigh 450 mg of hard carbon negative electrode material, 25 mg of conductive carbon black, and 20 mg of carboxymethyl cellulose, add appropriate amount of deionized water and use a planetary ball mill to mill for 2 h. Apply the milled slurry on the current collector, dry it in vacuum at 80 °C for 12 h, and cut it into negative electrode sheets with a diameter of 12 mm. Use metallic sodium as the counter electrode and reference electrode, use glass fiber diaphragm as the diaphragm, and use NaPF with a concentration of 1 mol / L as the electrolyte. 6 The solvent is a mixed solution of diethyl carbonate and ethylene carbonate (volume ratio is 1:1). The button cell is assembled in a glove box with an argon atmosphere. The electrochemical performance of the button cell is tested on a Xinwei battery test system. The charge and discharge voltage range is 0 to 2V, the current density is 0.5C, and 1C = 100mA / g.

[0091] Table 1

[0092]

[0093] The above examples prove that the porous hard carbon negative electrode material prepared by the preparation method provided by the present invention can enable the sodium ion battery to have better electrochemical performance.

[0094] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0095] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a hard carbon negative electrode material by regulating the microscopic pore structure, characterized in that: The steps include: Placing a hard carbon precursor material in a closed reactor for a preliminary reaction to obtain a pre-product, wherein the filling degree of the hard carbon precursor material in the closed reactor is greater than or equal to 40%, when the filling degree is 40%, the temperature of the preliminary reaction is 350° C.-450° C., and the temperature of the preliminary reaction is relatively reduced by 20° C.-25° C. for every 5% increase in the filling degree; Under a protective atmosphere, the pre-product is subjected to a first carbonization treatment and a second carbonization treatment in sequence to obtain a hard carbon negative electrode material.

2. The method for preparing a hard carbon negative electrode material for adjusting the microscopic pore structure according to claim 1, characterized in that: The filling degree of the hard carbon precursor material in the closed reactor is 50%-90%.

3. The method for preparing a hard carbon negative electrode material for adjusting the microscopic pore structure according to claim 1, characterized in that: The change in the filling degree of the reactants before and after the reaction in the closed reactor is 5%-10%.

4. The method for preparing a hard carbon negative electrode material with a microscopic pore structure according to any one of claims 1 to 3, characterized in that: The hard carbon precursor material includes at least one of a sugar material, a bio-based material, and a resin-based material.

5. The method for preparing a hard carbon negative electrode material with a microscopic pore structure according to any one of claims 1 to 3, characterized in that: The temperature of the preliminary reaction is 150° C.-500° C., the heating rate is 1° C. / min-10° C. / min, and the insulation time is 60 min-600 min.

6. The method for preparing a hard carbon negative electrode material for regulating the microscopic pore structure according to any one of claims 1 to 3, characterized in that: The temperature of the first carbonization treatment is 500° C.-700° C., the heating rate is 1° C. / min-10° C. / min, and the insulation time is less than or equal to 180 minutes.

7. The method for preparing a hard carbon negative electrode material for regulating the microscopic pore structure according to any one of claims 1 to 3, characterized in that: The temperature of the second carbonization treatment is 1000° C.-1500° C., the heating rate is 1° C. / min-5° C. / min, and the insulation time is less than or equal to 180 minutes.

8. A hard carbon negative electrode material obtained by the preparation method for adjusting the microstructure of a hard carbon negative electrode material according to any one of claims 1 to 7, characterized in that: The volume of the closed nanopores in the prepared hard carbon negative electrode material is 0.1 cm 3 / g-0.5cm 3 / g.

9. The hard carbon negative electrode material according to claim 8, characterized in that: The volume of the closed nanopores in the hard carbon negative electrode material is 0.15 cm 3 / g-0.4cm 3 / g.

10. A hard carbon negative electrode material as claimed in claim 8 or 9 for use in a sodium ion battery.

Citation Information

Patent Citations

  • Biomass-based hard carbon, preparation method thereof and application of biomass-based hard carbon in sodium-ion battery

    CN115020643A

  • Starch-based hard carbon sodium ion battery negative electrode material as well as preparation method and application thereof

    CN116544386A